High‐fidelity compression for high‐throughput photoacoustic microscopy systems. Issue 5 (14th March 2022) - Zafar, Mohsin; Manwar, Rayyan; Avanaki, Kamran
Abstract: Photoacoustic microscopic images can assist specialists in disease diagnosis by providing vascular information. However, the size of such data is usually extremely large (ie, gigabytes), and thus, a real‐time, efficient compression method can facilitate easy storage and transportation of these images. We have implemented multiple data compression methods in LabVIEW with a high compression ratio and execution times below the repetition rate of the pulsed laser. The qualitative and quantitative results of ex vivo and in vivo imaging with compression showed near‐identical images to uncompressed images, with significantly smaller size. Abstract : We have implemented multiple high speed data compression algorithms to facilitate efficient storage and transportation of high‐resolution data acquired from photoacoustic microscopy in real time. Ex vivo skin imaging of mouse and in vivo imaging of rat's brain were performed to demonstrate the capability of these data compression algorithms. Images before and after data compression were near identical.